Mainstreaming climate change into local governance: financing and budgetary compliance in selected local governments in Ghana. Issue 1 (2nd January 2018) - Musah-Surugu, Justice Issah; Owusu, Kwadwo; Yankson, Paul William Kojo; Ayisi, Emmanuel Kofi
ABSTRACT: Through an interpretive research paradigm, we investigated the extent to which six local governments across three administrative regions of Ghana have complied with mandated climate change financing and budgeting guidelines. Five interesting findings emerged. First, there is enormous evidence of climate change budgeting compliance across all six local governments despite weak compliance incentives. Second, local governments that are most vulnerable to the impacts of climate change are more willing to comply and also allocate more resources for adaptation-related activities than those that are less vulnerable. Third, local governments that complied least are likely to take ad hoc adaptation actions which are often uncoordinated and poorly monitored. These local governments are least likely to attract auxiliary funds that could provide additional resources for adaptation financing. Lastly, the evidence of compliance is only quantitative, presented in various local governments' fiscal documents, with no qualitative or other relevant explanatory factors on the extent of impact on adaptation.